COVID-19: Where Do We Go from Here? An Experience from Medical Students in India - Tanisha Kalra; Nikhita Kalra (International Journal of Medical Students, 2020)
We’ve all read about the repercussions of pandemics in the past centuries, but COVID-19 is the first one we’ve struggled through! As uncertainty prevails in this unprecedented lockdown, we have deliberated over our perspective of our country’s preparedness and evolving protocols, along with the brunt taken by the academic courses. Nevertheless, there’s always a silver lining to look for, as we escape from our overbearing deadlines!